Interfacial gradient M7C3 carbides precipitation behavior and strengthening mechanisms of stainless steel/carbon steel clad plates - Jihong Sun; Xuefeng Liu; Yaohua Yang; Wenjing Wang (Journal of Materials Research and Technology, 2022)
The mechanical incompatibilities between ferrite and martensite at the cladding interface of stainless steel (SS)/carbon steel (CS) clad plates can result in stress concentration and interface cracks. In this paper, 304 SS/Q235 CS clad plates were prepared by liquid-solid (L-S) composite casting, and the mechanical incompatibilities between ferrite and martensite reduced by constructing gradient carbides in the interfacial ferrite. The precipitation behavior of the gradient carbides was analyzed, and the strengthening mechanism was revealed. The ultimate strength of the SS/CS clad plates was 370 MPa when stretched perpendicular to the cladding interface, and the SS/CS clad plates fractured in the CS that was far from the cladding interface. The interfacial microstructures from the CS to the SS were ferrite, M7C3 carbides, and lath martensite, and the carbides content gradually decreased toward the CS. During the L-S composite process, a micro-melting region with decreased volume fraction of interdendritic liquid to the CS formed at the cladding interface. The C, Cr, and Ni mixed and diffused in the interdendritic liquid, and the gradient distribution of elements resulted in the precipitation of coherent M7C3 carbides whose volume fraction decreased toward the CS. The coherent strengthening and precipitation strengthening of carbides strengthened the interfacial ferrite and resulted in a gradient strengthening, which reduced the mechanical incompatibilities between ferrite and martensite at the cladding interface. Additionally, the gradient carbides changed the stress state at the cladding interface and improved the interfacial bonding strength.